2023
DOI: 10.1186/s12882-023-03058-9
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab as a treatment for C3 glomerulopathy: a single-center retrospective study

Abstract: Background C3 Glomerulopathy (C3G) is a rare glomerular disease caused by dysregulation of the complement pathway. Based on its pathophysiology, treatment with the monoclonal antibody eculizumab targeting complement C5 may be a therapeutic option. Due to the rarity of the disease, observational data on the clinical response to eculizumab treatment is scarce. Methods Fourteen patients (8 female, 57%) treated for C3 glomerulopathy at the medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The anti-C5 monoclonal antibody eculizumab [ 28 ] (Figs 1 and 2 ) has been tested in single C3G or Ig-MPGN patients, small retrospective series [ 29 , 30 ] and in an off-on-off-on study, the EAGLE (Evaluating the Morphofunctional Effects of Eculizumab Therapy in Primary Membranoproliferative Glomerulonephritis) trial [ 31 ], with mixed results (Table 3 ). In some patients, proteinuria improved and renal function stabilized; however, the response to treatment was mostly partial in the long-term and about half patients did not benefit from the treatment.…”
Section: Treatment Standardsmentioning
confidence: 99%
“…The anti-C5 monoclonal antibody eculizumab [ 28 ] (Figs 1 and 2 ) has been tested in single C3G or Ig-MPGN patients, small retrospective series [ 29 , 30 ] and in an off-on-off-on study, the EAGLE (Evaluating the Morphofunctional Effects of Eculizumab Therapy in Primary Membranoproliferative Glomerulonephritis) trial [ 31 ], with mixed results (Table 3 ). In some patients, proteinuria improved and renal function stabilized; however, the response to treatment was mostly partial in the long-term and about half patients did not benefit from the treatment.…”
Section: Treatment Standardsmentioning
confidence: 99%
“…4 While complement inhibitors have been proposed as potential diseasespecific therapies, recent studies of the C5 inhibitor eculizumab in C3G have not shown consistent efficacy. 5,6 The recent recognition of C3G as a distinct histopathological entity has allowed more precise characterizations of the underlying pathophysiology. Studies based on familial cases as well as animal models showed that constitutive activation of the alternative pathway is key to the development of the disease, mediated by factors including mutations in complement regulator genes and autoantibodies to enzymes in the complement cascade.…”
Section: Introductionmentioning
confidence: 99%